Development of smart chicken poultry farm - Mansor, Hasmah; Ahmad Ammar, Nor Azlin; Gunawan, Teddy Surya; Md Kamal, Mahanijah; Hashim, Ahmad Zawawi (IAES, 2018)
In Malaysia, most agriculture industries are still using conventional method to operate. All routines in monitoring and control of chicken poultry farm, for example, utilise man power where the source and energy are very limited. However, the demand from consumers towards the agricultural output is increasing day by day and requires more advanced farming technology in order to obtain maximum efficiency. This paper is focused on the development of smart chicken poultry farm to provide monitoring and control of the farm condition. The electronics, embedded systems and wireless technology are integrated with farm monitoring. Using Master-Slave concept, sensors are used to measure the ambient temperature, ammonia and humidity of the hall of chicken poultry for each slave. The sensors’ readings are then transmitted wirelessly over radio frequency by serial communication using HC-12 RF module to master for further data processing. The design process of both master and slave involved the interfacing of microprocessor, ATMEL ATMega328 with several analogue sensors, LCD, buzzer, relay output, monetary push button and light indicator. Based on the readings from the sensors, the microcontroller produced the output which is connected to the fan for better air ventilation in the chicken poultry farm. Furthermore, PID controller has been integrated to optimize the output control method, hence optimizing hall condition which results to better output for the farm. The system has been successfully implemented and tested at Myra Farm & Services, located at Kalumpang, Tanjung Malim, Perak, Malaysia.